0.2% Betamethasone Sodium Phosphate: A Multicenter, Randomized, Double-Masked Study to Compare Its Ocular Safety, Tolerability, and Efficacy to Vehicle in Cataract Surgery Subjects - Hosseini K; Gollamudi S; Reiser H; Walters T; Lindstrom RL (Clinical Ophthalmology, 2023)
Kamran Hosseini,1 Subba Gollamudi,2 Harvey Reiser,3 Tom Walters,4 Richard L Lindstrom5 1Surface Ophthalmics, Pleasanton, CA, USA; 2VRF Eye Specialty Group, Memphis, TN, USA; 3Eye Care Specialists, Kingston, PA, USA; 4Texan Eye, PA — Keystone Research, Austin, TX, USA; 5Minnesota Eye Consultants, Bloomington, MN, USACorrespondence: Kamran Hosseini, Surface Ophthalmics, Inc, 5000 Hopyard Road, Ste. 402, Pleasanton, CA, 94588, USA, Email khosseini@surfaceophthalmics.comPurpose: To compare the preservative-free corticosteroid 0.2% betamethasone sodium phosphate BID (SURF-201) to vehicle BID in patients undergoing routine cataract surgery.Methods: Phase 2, multicenter, randomized (1:1 ratio), double-masked, vehicle-controlled, parallel-group study in patients scheduled for uncomplicated cataract surgery without the aid of a femtosecond laser. Subjects instilled topical medications for 16 days beginning the day before cataract surgery (Day − 1), 1 dose administered at least 1 hour prior to cataract surgery (on Day 0) and 1 dose on the evening after cataract surgery, and then 2 doses administered each day through Day 15; patients were re-evaluated on Days 22 and 32 to ensure no rebound inflammation. Primary outcome was the difference in the proportion of subjects with anterior chamber cell (ACC) grade 0 between the two groups at Day 15. Secondary outcomes included pain scores and overall safety.Results: There was a statistically significant difference (P=0.004) in the proportion of subjects in the SURF-201 treatment group with an ACC grade of 0 at Day 15 (n=22/39 [56.4%]) compared to subjects in the vehicle treatment group (n=9/43 [20.9%]). There was no statistically significant difference (P=0.528) in the proportion of subjects in the SURF-201 treatment group who had a visual analog scale pain score of 0 at Day 15 (n=35/38 [89.7%]) compared to subjects in the vehicle group (n=33/40 [82.5%]). A slightly higher incidence of adverse events occurred in subjects in the SURF-201 treatment group (n=27/40 [67.5%]) compared to the vehicle treatment group (n=23/43 [53.5%]).Conclusion: SURF-201 is an effective topical, preservative-free corticosteroid when dosed BID for the treatment of postoperative inflammation and prevention of pain in a post-cataract population.Keywords: cataract, postoperative inflammation, corticosteroid, betamethasone sodium phosphate, preservative-free